Efforts to strengthen the resilience of the Pancasila ideology among the village community - Masrukhi Masrukhi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The purpose of this research is to determine how to strive for the resilience of the Pancasila ideology among village people. This research was carried out using a Qualitative Research approach, with the research setting in five villages around the State University of Semarang, namely Sekaran, Patemon, Pakintelan, Sukorejo, and Kalisegoro (Seppasuka) Villages, Gunungpati District, Semarang City. This study found that social capital in society, in the form of kinship ties, social networks, and local wisdom values, can be empowered as a vehicle for socialization and internalization of Pancasila values in an effort to strengthen ideological communities.